2020
DOI: 10.1007/s42770-020-00279-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological survey on sporotrichosis-infection in rural areas of the south of Minas Gerais State, Brazil

Abstract: Sporotrichosis is a subcutaneous mycosis caused by traumatic inoculation into the skin by fungi species of the genus Sporothrix. The disease has different clinical manifestations (cutaneous, lymphocutaneous, and disseminated), and can also progress to a systemic infection. Despite having a worldwide distribution, sporotrichosis is most prevalent in tropical and subtropical countries. In Brazil, reports of the disease are higher frequent, where cases of the disease were found in Rio de Janeiro, Sao Paulo, Curit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A total of 68 publications with 11,050 cases of sporotrichosis were found in South America [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 …”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
“…A total of 68 publications with 11,050 cases of sporotrichosis were found in South America [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 …”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
“…conidia into skin or mucosa [ 11 , 12 , 13 , 14 , 15 , 16 ]. Infection with this fungus is related to areas of the body exposed to trauma [ 17 , 18 ]. Historically, sporotrichosis was known as the “gardener’s mycosis”, classically associated with soil manipulation activities, whether due to occupational or leisure reasons [ 9 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genetic sequencing studies confirmed that S. schenckii is a complex composed of cryptic species: S. albicans, S. brasiliensis, S. globosa, S. luriei, S. mexicana, and S. schenckii [ 17 , 31 , 32 , 33 ]. S. brasiliensis and S. schenckii are common in Brazil, S. mexicana is present in Mexico, and S. globosa is common in countries such as China, India, Japan, the USA, Spain and Italy [ 17 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baptista et al [9] report here its applicability for feline sporotrichosis diagnosis and/or therapeutic follow-up. Grisolia et al [10] present a seroepidemiological survey of the prevalence of sporotrichosis in four rural locations in the south of Minas Gerais state, Brazil.…”
mentioning
confidence: 99%